Code domain power measuring system receiver - Basavaraju, B. M. (2008)
In this dissertation, the design and implementation of a code domain power-measuring receiver for measuring pilot signals in CDMA systems are presented. The receiver searches for pilot signals by digitally correlating the received signal with known locally generated pilot signal. By systematically changing the phase of this locally generated pilot signal, the receiver scans the received signal to identify all possible signs of pilot signal activities.